1984
DOI: 10.2136/sssaj1984.03615995004800010024x
|View full text |Cite
|
Sign up to set email alerts
|

Strength Characteristics of Three Indurated Horizons in Massachusetts

Abstract: Identification of fragipans is often difficult due to the lack of quantitative differentiating criteria. The unconfined compression (UC) test was used to characterize strength properties of three indurated horizons. Tests were performed in the laboratory on undisturbed core samples equilibrated to one of four moisture conditions: wet, 0.1 MPa, 0.5 MPa, or air‐dried. Fragipans developed in basal till exhibited maximum UC strength values of about 100 kPa at moisture contents < 0.10 kg kg−1 and minimum UC stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Strong depletion and preferential loss of all forms of extractable iron and manganese relative to aluminium in the greyish zones, with enrichment in adjacent narrow reddish borders (Table 2), indicates a redox related process. This micromorphological and chemical evidence supports the process of development proposed in several American fragipan studies (Gile, 1958;Miller et al, 1971;Pickering & Veneman, 1984) involving lateral diffusion of manganous and ferrous ions mobilized during periods of localized waterlogging in polygonal zones. The process has affected both fissure infill and fissure walls so that the width of the grey zones (up to 2cm) is considerably greater than that of the infilled fissures (0.5 cm or less).…”
Section: Origin Of Greyish Polygonal Patterningsupporting
confidence: 86%
See 1 more Smart Citation
“…Strong depletion and preferential loss of all forms of extractable iron and manganese relative to aluminium in the greyish zones, with enrichment in adjacent narrow reddish borders (Table 2), indicates a redox related process. This micromorphological and chemical evidence supports the process of development proposed in several American fragipan studies (Gile, 1958;Miller et al, 1971;Pickering & Veneman, 1984) involving lateral diffusion of manganous and ferrous ions mobilized during periods of localized waterlogging in polygonal zones. The process has affected both fissure infill and fissure walls so that the width of the grey zones (up to 2cm) is considerably greater than that of the infilled fissures (0.5 cm or less).…”
Section: Origin Of Greyish Polygonal Patterningsupporting
confidence: 86%
“…Most North American authors reject the permafrost hypothesis and favour development in a temperate environment. Compaction has been variously attributed to contraction under slight overburden pressures; rearrangement of soil constituents on wetting and drying; additions of illuvial material along contraction fissures; pressures generated by tree roots; or inheritance from till fabrics (Soil Survey Staff, 1975;Pickering & Veneman, 1984;Bryant, 1989). Several studies support the clay bridge hypothesis to explain brittleness when moist (Miller et al, 1971;Wang et al, 1974;Lindbo & Veneman, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In other experiment years, the highest values of soil bulk density were caused from low soil moisture content (110 g kg -1 ) and the lowest soil bulk density values occurred in 2001 and 2004 when high soil moisture content (210 g kg -1 ) was present at compaction application. In experiments of Pickering and Veneman (1984), soil dry density increased to the soil moisture content 0.11-0.12 kg kg -1 and started to decrease at higher moisture contents.…”
Section: Compaction Effect On Soil Propertiesmentioning
confidence: 92%
“…lost 79% of its hardness. The mechanism of soil strength reduction with increasing wetness is explained by Pickering and Veneman (1984). They reported that the partial dissolution of the bonding agent between peds and particles, and the reduction of interparticulate friction by films of moisture that import as a lubricant effect.…”
Section: Petrogypsipan Sandy Gypsic Shallow Slightly Thick Moderately Indurated Aquicmentioning
confidence: 99%